Hayden White and the Problem of Historical Referentiality in Markan Narrative - Alan Kirk (Svensk Teologisk Kvartalskrift, 2023)
In his Story as History – History as Story, Byrskog applied the powerful explanatory model of oral history to the formation of the tradition and to the narrative projects of the evangelists. The model needs to be taken further to confront the view among Gospel narrative critics that narrative formation in the Gospel of Mark is such as to render its materials opaque to historical enquiry. Narrative criticism works with a schematic binary between Mark's raw historical source materials on the one hand and his meaning-bestowing imposition of a narrative emplotment upon them on the other. This has strong affinities to Hayden White's model for narrative history-writing. White regards narrative emplotment as the historian's imposition upon past events that taken in themselves constitute nothing more than an "ephemeral flow of events", awaiting the historian's impress of narrativity. Moral meaning is an ideological imposition upon a sequence of events by virtue of the narrative historian's emplotment of that sequence into a story. Powerful critiques of White by Paul Ricœur and Holocaust historians have called into question schematic distinctions between historical reality and its narrative representations. Not only are narrative representations grounded in memory; they are distinguished by a referential intention towards a real past.